Process for the continuous magnetic removal of microplastics present in aqueous matrices
The use of a venturi device to form microplastic/magnetic iron material aggregates and subsequent magnetic separation provides an efficient method for removing microplastics from aqueous streams, overcoming existing inefficiencies and scalability issues.
Patent Information
- Application Number
- JP2024545211
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-27
- Filing Date
- 2023-01-26
- Publication Date
- 2025-03-18
AI Technical Summary
Current methods for removing microplastics from aqueous streams are inefficient, particularly for small microplastics, and often require specialized equipment and long analysis times, limiting their industrial scale expansion and effectiveness in high water flow rates.
The process involves using a venturi device to instantaneously form microplastic/magnetic iron material aggregates by bringing microplastics into close contact with magnetic iron material particles, followed by separation using a magnetic filter.
This method achieves high efficiency in separating microplastics regardless of their size or composition, with yields exceeding 76% for microplastic separation and 94% for magnetite recovery, while significantly reducing processing time and requiring low-cost, simplified equipment.
Smart Images

Figure 2025507273000008 
Figure 2025507273000009 
Figure 2025507273000010
Abstract
Description
[Technical field]
[0001] The present invention relates to a process that allows the removal of microplastics present in an aqueous stream by the immediate formation of microplastic / magnetic ferrous material agglomerates as a result of preferred intimate contact in the throat of a Venturi device and the subsequent separation of the formed agglomerates by application of a magnetic filter. [Background technology]
[0002] Due to the excellent properties of plastics, among which the ease of molding, high mechanical and chemical resistance, and low cost stand out, plastics are widely used both in industry and society as a whole. Since the development of the first synthetic polymers in the mid-20th century, the production of these synthetic polymers has not stopped growing. In 2019, the global production of plastics reached 370 million tons (PlasticsEurope, 2020), and the production of plastics is expected to double in the next 20 years (MacArthur, DE et al., The New Plastics Economy: Rethinking the Future of Plastics. World Economic Forum. (2016)). Although plastics are certainly useful, the generation of plastic waste and its improper management are significant environmental issues.
[0003] Removal of plastics is not a problem when the plastics are large in size. However, with use, plastics decompose, generating smaller pieces of plastic that are more difficult to remove (especially when the pieces have a diameter of millimeters). Microplastics are defined as plastic particles with a size of less than 5 mm (Bergmann, M. et al., Marine Anthropogenic Litter (2015) Springer) and are traces of plastics that are widespread in the environment. Microplastics have been found in virtually all ecosystems on Earth, including inland and marine waters, sediments, air, and soil (Grbic, J. et al., Environmental Science and Technology Letters 6 (2019) 68-72). They are therefore present in living organisms (Cole, M. et al., Nature Scientific Reports 4: 4528 (2014) 1-8; Wieczorek, A. M. et al., Environmental Science and Technology 53 (2019) 5387-5396), essentially aquatic organisms, so there is considerable concern about the potential damage their presence could have both in humans and in fauna (Wright, S. Let al., Environmental Science and Technology 51 (2017) 6634-6647; Cox, K. D. et al., Environmental Science and Technology 53 (2019) 7068-7074).
[0004] It is estimated that 80% of the microplastics present in the ocean originate directly from rivers (Li, J. et al. Water Research 137 (2018) 362-374). And rivers are the main recipients of effluents from urban and industrial wastewater treatment plants (WWTPs), which have been identified as an important source of introducing microplastics into the aquatic environment (Li, J. et al. Water Research 137 (2018) 362-374). In this aspect, the development of equipment that allows the treatment of microplastic-contaminated water is clearly a relevant challenge.
[0005] On the other hand, in order to assess the true impact of microplastics and their distribution in the environment, as well as to formulate specific regulations in this field, it is essential to carry out a proper quantification and characterization of these particles in the different aqueous matrices that may contain them (WWTP effluents, drinking water, rivers, lakes, reservoirs, and oceans, among others). The analysis of these particles is particularly complex given their very heterogeneous size, shape, color, density, and chemical composition. In a recent literature review (Koelmans, AA et al. Water Research 155 (2019) 410-422), 50 papers that studied the presence of microplastics in inland waters and drinking water were analyzed. It was concluded that many of the papers could not be considered completely reliable. The biggest challenge is the very small microplastics, i.e. those with a size of less than 300 μm. For example, sampling with a net with a pore size of 80 μm instead of 330 μm resulted in measurements of concentrations 250 times higher (Dris, R. et al. Environmental Chemistry 12 (2015) 592-599). Given the series of published studies on the presence of microplastics in inland waters, there is a clear need to develop effective sampling systems for the analysis of microplastics. Indeed, a recent World Health Organization report entitled "Microplastics in drinking-water" (World Health Organization (2019) ISBN 978-92-4-151619-8) highlighted the development of methods for sampling and analysis of microplastics as a necessary priority in research.
[0006] Filtration or sieving is the most common method for separating microplastics from aqueous matrices (Prata, JC et al. Trends in Analytical Chemistry 110 (2019) 150-159). The pore size of the filters or sieves used varies widely and logically determines the size of microplastics that can be separated. Nevertheless, very small pore sizes are usually avoided because they cause clogging problems due to the presence of other solids in suspension in the water, and moreover, using very small pore sizes consumes a lot of time. Therefore, small pore sizes (0.45-100 μm) are usually only used in the analysis of particularly clean aqueous matrices such as groundwater and drinking water (Koelmans, AA et al. Water Research 155 (2019) 410-422). In that sense, Neston nets with a pore size of 333 μm and plankton nets with a pore size of 100 μm are the most commonly used directly for sampling (Stock, F. et al. Trends in Analytical Chemistry 113 (2019) 84-92; Prata, JC et al. Trends in Analytical Chemistry 110 (2019) 150-159).
[0007] There are less common methods to separate and further directly quantify microplastics from the aqueous matrix, for example electrostatic separators (Felising, S. et al. Environmental Pollution 234 (2018) 20-28) and flow cytometry (Sgier, L. et al. Nature Communication 7 (2016) 11587). Nevertheless, they require specialized equipment and long analysis times, in addition to entailing high costs. And most importantly, they do not allow the characterization of microplastics, but rather only the counting of particles.
[0008] The development of microplastic sampling devices based on the application of a magnetic separation process after coating microplastics with magnetic nanoparticles shows promising potential. Recent studies (ES 2 796 998 A1 and WO 2020 / 240069 A1 and Grbic, J. et al., Environmental Science and Technology Letters, 6 (2019) 68-72) have shown that the separation of microplastics from water is highly effective, regardless of the nature and size of the microplastics, by interaction with magnetic nanoparticles and subsequent application of a magnetic field. Although this method has great advantages compared to traditional filtration methods, it is well known in the state of the art that the use of magnetic nanoparticles for the separation of organic compounds requires a given contact time for the interaction to occur ((ES 2 796 998 A1 and WO 2020 / 240069 A1, Razali, SZ et al., IOP Conf. Series: Earth and Environmental Sciences, 596 (2020) 012052). In the specific case of microplastics, in addition to the contact time, the process requires an intimate interaction between the magnetic material and the microplastics, which limits its industrial scale-up. Therefore, the development of a system that allows the formation of aggregates to be achieved instantaneously, working in direct flow and at high water flow rates, represents an important breakthrough in this field.
[0009] Considering this background, the development of a system that allows for the efficient, rapid and cost-effective removal of microplastics present in aqueous streams, regardless of their composition and size, by the instantaneous formation of aggregates in aqueous matrices of different nature, would represent an important finding in a field where treatment or sampling at direct flow and high water flow rates is currently clearly limited. Summary of the Invention
[0010] The inventors have unexpectedly discovered that the application of the Venturi effect causes the instantaneous formation of microplastic / magnetic iron material aggregates when a water stream containing microplastics is brought into contact with another water stream containing magnetic iron material particles. This discovery is particularly surprising since the Venturi effect is known to achieve very strong mixing. Indeed, due to the intensity of mixing of the streams contacting each other in a Venturi device, one skilled in the art would expect the particles present in both streams to collide, but one would not expect the magnetic material particles to stably attach to the microplastics under such conditions, but rather to disintegrate them. This discovery can be applied both to the design of treatment systems that allow the removal of microplastics from contaminated aqueous streams, such as sampling of microplastics contained in an aqueous matrix or stream, and to microplastic analysis processes.
[0011] As shown in the examples, the formation of microplastic / magnetic material aggregates in the Venturi device was practically instantaneous, with a yield of 100%. The system also proved to be highly efficient in the separation of microplastics in a magnetic filter, with a yield of more than 76%, and in the recovery of magnetite, with a yield of more than 94%, regardless of the nature or size of the microplastics. The system for separating microplastics of the present invention is particularly advantageous with respect to other methods included in the state of the art, since it involves a significant reduction in the time required to achieve the separation of microplastics from a polluted aqueous stream. A further advantage of the process of the present invention is the simple equipment required and the low cost of the materials used. Finally, the system showed a high reproducibility of the results obtained.
[0012] Thus, the present invention provides a process for separating microplastics from an aqueous matrix, comprising: a) providing an aqueous matrix containing microplastics; b) providing a suspension of magnetic ferrous particles in water; c) passing the aqueous matrix of step a) through a Venturi device and contacting it at the throat of the Venturi device with the suspension of magnetic material particles in water from step b) to form microplastic / magnetic ferrous material particle agglomerates; d) separating the free magnetic iron particles and the microplastics / magnetic iron particle agglomerates formed in step c) from the water by means of a magnetic filter; The present invention relates to a process comprising: [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a diagram of the Venturi device used, with corresponding dimensions for the channeling and throat. [Diagram 2] Particle size distribution of magnetic iron mineral (magnetite) used in the examples. [Diagram 3] Electron microscope images of polystyrene particles (left) and polystyrene / magnetite aggregates formed after passing through a venturi (right). [Figure 4] Detailed electron microscope images (0.1 μm resolution) of polystyrene particles (left) and polystyrene / magnetite aggregates formed after passing through the Venturi (right). [Diagram 5] Electron microscope images of polyethylene particles (left) and polyethylene / magnetite aggregates formed after passing through a venturi (right). [Figure 6] Detailed electron microscope images (0.1 μm resolution) of polyethylene particles (left) and polyethylene / magnetite aggregates formed after passing through the Venturi (right). [Figure 7] Electron microscope images of polypropylene particles (left) and polypropylene / magnetite aggregates formed after passing through a venturi (right). [Figure 8] Detailed electron microscope images (0.1 μm resolution) of polypropylene particles (left) and polypropylene / magnetite aggregates formed after passing through the Venturi (right). [Figure 9] Electron microscope images of a sand particle (left) and after passing through a Venturi (right). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention provides a process for separating microplastics from an aqueous matrix, comprising: a) providing an aqueous matrix containing microplastics; b) providing a suspension of magnetic ferrous particles in water; c) passing the aqueous matrix of step a) through a Venturi device and contacting it at the throat of the Venturi device with the suspension of magnetic material particles in water from step b) to form microplastic / magnetic ferrous material particle agglomerates; d) separating the free magnetic iron particles and the microplastics / magnetic iron particle agglomerates formed in step c) from the water by means of a magnetic filter; The present invention relates to a process comprising:
[0015] The first step of the process, step a), is to provide an aqueous matrix containing microplastics.
[0016] In the context of the present invention, the term "microplastic" or "microplastics" refers to plastic material having an average diameter of less than 5 mm, preferably comprised in the range of 0.1 μm to 5 mm, more preferably in the range of 0.1 μm to 1 mm, even more preferably in the range of 0.1 μm to 500 μm, even more preferably in the range of 100 μm to 250 μm. Measuring the size of the microplastic involves its prior separation from the aqueous matrix by vacuum filtration using a microporous membrane filter with a pore size of 0.1 μm or less, and its subsequent drying at room temperature or in a drying oven at a temperature of 100 ° C or less. The filter containing the microplastic is then analyzed by scanning electron microscopy, for example using the conditions described in the examples. The length and width of the microplastic are measured and the size of the largest dimension (length) is assigned. The average diameter is defined as the average length of the microplastic particles (the sum of the lengths of the analyzed particles out of the number of particles analyzed).
[0017] Microplastics can be formed from any plastic material, preferably synthetic organic polymers, such as polyethylene terephthalate (PET), polyethylene (PE), including high density polyethylene (HDPE) and low density polyethylene (LDPE), polyvinyl chloride (PVC), polypropylene (PP), polystyrene (PS), polycarbonate (PC), polyurethane (PU), and combinations thereof.
[0018] "Polyethylene terephthalate" or "PET" is a polymer obtainable by the reaction of polycondensation between terephthalic acid and ethylene glycol. Polyethylene terephthalate has the following structure: [ka]
[0019] "Polyethylene" or "PE" refers to a polymer obtainable by the polymerization of ethylene. Polyethylene has the following structure: [ka]
[0020] "High density polyethylene" or "HDPE" refers to polyethylene whose density falls within the range of 0.930 to 0.970 g / mL. "Low density polyethylene" or "LDPE" refers to polyethylene whose density falls within the range of 0.917 to 0.930 g / mL.
[0021] "Polyvinyl chloride" or "PVC" refers to a polymer obtainable by polymerization of vinyl chloride. Polyvinyl chloride has the following structure: [ka]
[0022] "Polypropylene" or "PP" refers to a polymer obtainable by polymerization of propylene. Polypropylene has the following structure: [ka]
[0023] "Polystyrene" or "PS" refers to a polymer obtainable by polymerization of styrene. Polystyrene has the following structure: [ka]
[0024] "Polycarbonate" or "PC" refers to a polymer containing functional groups linked by carbonate groups (-O-C=O)-O-), such as diallyldiethylene glycol polycarbonate or, most commonly, bisphenol A polycarbonate, the structure of which is shown below. [ka]
[0025] "Polyurethane" or "PU" refers to a polymer obtained by condensation of a polyol, among which ethylene glycol and propylene glycol stand out, with a polyisocyanate, among which methylene diphenyl diisocyanate (MDI) and toluene diisocyanate (TDI), resulting in urethane groups (-NH-(C=O)-O-) in the structure of the polymer. Polyurethanes are widespread due to the range of polyisocyanates and polyols that can be used to form them.
[0026] In a preferred embodiment, the microplastics are selected from the group consisting of polystyrene, polyethylene including high and low density polyethylene, polyethylene terephthalate, polyvinyl chloride, polycarbonate, polyurethane, and mixtures thereof; more preferably, selected from the group consisting of polystyrene, polyethylene including high and low density polyethylene, polypropylene, polyethylene terephthalate, and mixtures thereof; even more preferably, selected from the group consisting of polystyrene, polyethylene including high and low density polyethylene, polypropylene, and mixtures thereof; even more preferably, selected from the group consisting of polystyrene, polypropylene, and mixtures thereof; most preferably, selected from the group consisting of polystyrene, polypropylene, and mixtures thereof. An advantage of the process of the present invention is its universal character, since magnetic separation is effective regardless of the chemical nature of the microplastics.
[0027] The expression "aqueous matrix" refers to a composition containing water as its main component, preferably at least 80% by weight, more preferably at least 85%, even more preferably at least 90%, even more preferably at least 95% water relative to the total weight of the composition. The aqueous matrix may further contain other substances already dissolved (e.g. salts such as NaCl) or in suspension. In particular, the aqueous matrix is selected from the group consisting of wastewater (including domestic, urban, industrial, agricultural and livestock breeding wastewater), sea water, river water, lake water, ground water, tap water or mixtures thereof. Thus, among others, wastewater purification plants, drinking water treatment plants, agro-food industries (e.g. fish farms), sources of water for human consumption, water facilities for recreational purposes (e.g. swimming pools) are facilities of interest for applying the process described in the present invention. The aqueous matrix comprises microplastics and may further comprise non-plastic organic particles. Optionally, the aqueous matrix may further comprise inorganic particles. Thus, in one embodiment, the aqueous matrix comprises microplastics and non-plastic organic particles. In another embodiment, the aqueous matrix comprises microplastics, non-plastic organic particles, and inorganic particles.
[0028] The expression "non-plastic organic particles" or "non-plastic organic solid particles" refers to particles that can have any shape, whose average diameter is in the range of 0.1 μm to 1 cm, preferably 0.1 μm to 5 mm, 0.1 μm to 5 mm, preferably 0.1 μm to 1 mm, more preferably 0.1 μm to 500 μm, even more preferably 100 μm to 500 μm, even more preferably 100 μm to 250 μm, that are not made of plastic material, and whose average diameter is the average length (sum of the lengths of the analyzed particles out of the number of analyzed particles), and whose length is the largest dimension of each particle. Examples of plastics are the same as those described for microplastics. Examples of non-plastic (organic) material particles are of plant origin (leaves, branches, seeds, fruits, etc.), of animal origin (bones, microcrustaceans, larvae, animal remains, etc.), of fungal origin, etc. The size of the particles can be determined in the same way as described for microplastics.
[0029] The expression "inorganic particles" or "inorganic solid particles" refers to particles that can have any shape, whose average diameter is in the range of 0.1 μm to 1 cm, preferably 0.1 μm to 5 mm, preferably 0.1 μm to 5 mm, more preferably 0.1 μm to 1 mm, more preferably 0.1 μm to 500 μm, even more preferably 100 μm to 500 μm, even more preferably 100 μm to 250 μm, are of mineral origin, and whose average diameter is the average length (sum of the lengths of the analyzed particles out of the number of analyzed particles), the length being the largest dimension of each particle. Examples of inorganic particles are sand, clay, insoluble salts, metal oxides, etc. The size of the particles can be determined in the same way as described for microplastics.
[0030] In certain embodiments, the size of the non-plastic organic and inorganic particles is in the same range as the size of the microplastics, preferably all of them having an average diameter of 100 μm to 250 μm.
[0031] Preferably, the pH of the aqueous matrix should be between 1 and 13, more preferably between 2 and 12, more preferably between 3 and 10, more preferably between 5 and 9, even more preferably between 6 and 8, and most preferably about 7. The pH of the aqueous matrix can be adjusted by adding a base, such as sodium hydroxide, potassium hydroxide or sodium carbonate, among others, or an acid, such as nitric acid, hydrochloric acid or sulfuric acid, among others, until a pH value within the range defined above is reached. The pH can be determined by a pH meter.
[0032] The process of the present invention allows for the separation of microplastics regardless of the electrical conductivity of the water. It is effective for both water with a low level of conductivity of less than 0.05 μS / cm and salt water with a high level of conductivity of 50 mS / cm. The term "electrical conductivity" refers to the ability of any material to conduct electric current. Electrical conductivity can be determined by a conductivity meter.
[0033] Preferably, the concentration of solid particles, including microplastics, in suspension in the aqueous matrix should be between 0.1 mg / L and 10,000 mg / L, more preferably between 1 mg / L and 1,000 mg / L, and even more preferably between 10 mg / L and 100 mg / L. The solid particles in suspension can be determined using processes known to those skilled in the art, such as gravimetric methods based on retaining solid particles on glass fiber filters ("Standard methods for the examination of water and wastewater", "2540 Solids" (APHA, AWWA, WPCF, 1992); Standard UNE-IN 872:2006 Water quality. Determination of suspended solids. Method by filtration through glass fiber filters).
[0034] The solid particles, including microplastics, present in the aqueous matrix are preferably determined, as their amount and composition serve to determine the amount of magnetic iron material, preferably magnetite, to be added in step b).
[0035] The concentration of microplastics in suspension in the aqueous matrix should preferably be between 0.1 mg / L and 10,000 mg / L, more preferably between 1 mg / L and 1,000 mg / L, even more preferably between 10 mg / L and 100 mg / L.
[0036] The process of the present invention requires in step a) providing an aqueous matrix containing microplastics. The aqueous matrix is continuously provided in step a) of the process of the present invention. The flow rate of the provided aqueous matrix is preferably 0.01-1000 L / s, preferably 0.01-100 L / s, even more preferably 0.01-10 L / s, even more preferably 300-600 L / h, even more preferably 400-500 L / h.
[0037] Step b) consists in providing a suspension of magnetic iron material particles in water.
[0038] The term "magnetic iron material" refers to any natural or synthetic solid substance that contains at least one iron species and has magnetic properties, i.e., is attracted by a magnet. In preferred embodiments, the magnetic iron material is inorganic. In certain embodiments, the magnetic iron material is uncoated, i.e., bare magnetic material particles. Preferably, the magnetic iron material has a molecular weight of between 5 emu / g and 100 emu / g (5·10 3 A / m and 10 5 A / m), more preferably between 30 emu / g and 90 emu / g (30·10 3 A / m and 90·10 3 A / m), and even more preferably between 65 emu / g and 90 emu / g (65·10 3 A / m and 90·10 3A / m), most preferably between 70 emu / g and 90 emu / g (70·10 3 A / m and 90·10 3 The magnetic properties of the magnetic iron material can be determined using a magnetometer equipped with a SQUID (Superconducting Quantum Interference Device) sensor. The magnetization (M) of the magnetic iron material is measured at room temperature in the range of -10000 to 10000 Oe (corresponding to -797700 to 797700 A / m) depending on the applied external magnetic field (H). The magnetic saturation value of the material is the value of M reached when any subsequent increase in H does not cause an increase in the magnetization of the material. Preferably, the iron material has an iron content of at least 10% by weight, preferably at least 20% by weight, more preferably at least 25% by weight, even more preferably at least 30% by weight, even more preferably at least 35% by weight, even more preferably at least 40% by weight, even more preferably at least 45% by weight, even more preferably at least 50% by weight, even more preferably at least 55% by weight, even more preferably at least 60% by weight, even more preferably at least 65% by weight. The percentage of iron can be determined using a total reflection X-ray fluorescence (TXRF) spectrometer using the method described in the Examples.
[0039] Preferably, the magnetic iron material comprises an iron species selected from the group consisting of Fe(II), Fe(III), metallic Fe, and mixtures thereof. One example is, inter alia, magnetite (ferrous oxide-ferric oxide FeO Fe 2 O 3 It is formed by Fe 3 O 4 (sometimes used as a compound), maghemite (γ-Fe 2 O 3 ), ilmenite (FeTiO 3 ) and pyrrhotite (Fe 0,8-1 In a preferred embodiment, the magnetic iron material is the mineral magnetite.
[0040] The use of magnetic iron minerals, and in particular magnetite, is advantageous from an economic and environmental standpoint, as it is an abundant, environmentally friendly material that is easily separated from the aqueous matrix.
[0041] The magnetic iron material is in the form of particles. The term "particles" refers to magnetic iron minerals in the form of powders or granules with an average diameter of less than 5 mm, preferably comprised between 0.05 μm and 5 mm, more preferably between 0.05 μm and 1 mm, even more preferably between 0.05 μm and 500 μm, even more preferably between 0.05 μm and 100 μm, even more preferably between 0.1 μm and 10 μm, even more preferably between 0.1 μm and 5 μm, even more preferably between 0.1 μm and 1 μm, even more preferably between 0.1 μm and 0.5 μm, most preferably between 0.1 μm and 0.3 μm. Preferably, the particle size distribution must be sufficiently narrow in the established size range. The determination of the particle size and distribution of the magnetic iron material can be carried out, for example, by scanning electron microscopy using the conditions described in the examples. The length and width of the microplastics are measured and the size of the largest dimension (length) is assigned. The average diameter is defined as the average length of the longest dimension of each magnetic ferrous material particle (the sum of the lengths of the analyzed particles out of the number of particles analyzed). For determining the particle size distribution, it is appropriate to use the statistics D10, D50, and D90, which capture 10%, 50%, and 90% of the accumulated particles by volume. In the preferred range, D10 (indicating that 10% of the particles in the sample by volume have a diameter smaller than this value) is 0.3 μm or less, D50 (indicating that 50% of the particles in the sample by volume have a diameter smaller than this value, representing the average particle size) is 0.50 μm or less, and D90 (indicating that 90% of the particles in the sample by volume have a diameter smaller than this value) is 0.8 μm or less. In the most preferred ranges, D10 (indicating that 10% by volume of the particles of the sample have a diameter smaller than this value) is 0.15 μm or less, D50 (indicating that 50% by volume of the particles of the sample have a diameter smaller than this value, representing the average particle size) is 0.20 μm or less, and D90 (indicating that 90% by volume of the particles of the sample have a diameter smaller than this value) is 0.35 μm or less. The magnetic iron material particles can be obtained by crushing the material and then sieving it into the size ranges mentioned above.The size of the magnetic ferrous material particles refers to the average diameter of the particles determined in dry conditions, without taking into account agglomeration of the magnetic material particles when suspended in an aqueous matrix.
[0042] The term "suspension of magnetic iron material" refers to a dosage of fully wetted magnetic iron material, preferably magnetite, suspended in water. The mass ratio of magnetic iron material / water, preferably magnetite / water, must be comprised between 1 mg / kg and 10 kg / kg, preferably between 1 mg / kg and 1 kg / kg, more preferably between 10 mg / kg and 100 g / kg, most preferably between 100 mg / kg and 10 g / kg. The suspension of magnetic iron material, preferably magnetite, in water can be produced by any mixing process, from using mechanical agitators of propeller or turbine type, where the stirring speed keeps the magnetic iron material particles, preferably magnetite, in suspension, due to the effect of rotation, to using rotary or piston pumps, where the speed of the propelled water creates a balance of forces between friction with the water and the weight of the particles, meaning that the particles are not deposited in a container, where they settle, and the particles are kept suspended in the water.
[0043] In particular, the suspension of magnetic iron material particles in step b) has a concentration of magnetic iron material particles of 0.1-1000 g / L, preferably 1-100 g / L, even more preferably 5-20 g / L, even more preferably 10 g / L.
[0044] The process of the present invention requires in step b) providing a suspension of magnetic material particles in water. The suspension is continuously provided in step b) of the process of the present invention. The flow rate of the provided suspension is preferably 0.001-100 L / s, preferably 0.001-10 L / s, preferably 0.001-1 L / s, even more preferably 5-50 L / h, even more preferably 10-30 L / h.
[0045] Step c) involves passing the aqueous matrix of step a) through a Venturi device and contacting it in the throat of the Venturi device with the suspension of magnetic particles in water from step b) to form microplastic / magnetic iron particle agglomerates, which includes the incorporation of magnetic iron particles into the aqueous matrix initially provided to form agglomerates between the microplastics and the magnetic iron particles.
[0046] The term "microplastic / magnetic ferrous particle agglomerates" or "microplastic / magnetic ferrous particle agglomerates" refers to clusters of particles formed by microplastics and magnetic ferrous particles due to interactions between them.
[0047] The concentration of the magnetic iron material in the throat of the venturi when the aqueous matrix of step a) and the suspension of step b) are mixed in step c) must be comprised between 1 mg / L and 100 g / L, preferably between 1 mg / L and 10 g / L, more preferably between 1 mg / L and 1 g / L, more preferably between 10 mg / L and 100 mg / L. Preferably, the microplastic / magnetic iron material concentration ratio in the throat of the venturi device is comprised between 1 mg microplastic / 0.001 mg magnetic iron material and 1 mg microplastic / 0.1 g magnetic iron material, preferably between 1 mg microplastic / 0.01 mg magnetic iron material and 1 mg microplastic / 100 mg magnetic iron material, more preferably between 1 mg microplastic / 0.1 mg magnetic iron material and 1 mg microplastic / 10 mg magnetic iron material.
[0048] These mass ratios and concentrations can be achieved at the flow rates for providing the aqueous matrix in step a) and for providing the suspension of magnetic material in step b) as defined above.
[0049] Step c) of passing the aqueous matrix of step a) through a Venturi device and contacting it in the throat of the Venturi device with the suspension of magnetic material particles in water from step b) to form microplastic / magnetic ferrous material particle agglomerates surprisingly contemplates the use of a Venturi device to achieve instantaneous formation of the microplastic / magnetic ferrous material agglomerates.
[0050] The aqueous matrix of step a) and the suspension of magnetic material particles in water of step b) are transported in step c) at the same flow rates as provided in steps a) and b), respectively.
[0051] The terms Venturi device, Venturi tube, Venturi or Venturimeter refer to a pipe that is first reduced in diameter and then restored to a second pipe that allows to exploit the properties of the Venturi effect, connected at a point with a minimum diameter, i.e. the throat. The reduction in the cross section of the Venturi typically has an angle of 15° to 25°, and the restoration of the cross section is typically performed at an angle between 5° and 15°. The angle must be smooth to avoid losses of energy in the fluid due to friction against the walls of the Venturi. In particular, the reduction in the diameter of the pipe in the throat of the Venturi device is 75% to 99%, preferably 80% to 95%, more preferably 85% to 90% of the diameter of the pipe before the throat (i.e. before the start of the reduction in the cross section of the pipe).
[0052] The Venturi effect arises due to the conservation of both mass and energy. In the case of mass, the continuity equation applies (the mass flow rate entering the pipe is the same as the mass flow rate leaving the pipe), and in the case of energy, the mechanical energy balance (formulated by Bernoulli, but which considers the sum of the different forms that mechanical energy can have, i.e. pressure, kinetic, or potential energy, must be conserved, i.e. can be transformed into another energy) applies. Thus, when directing a fluid through a pipe, according to the continuity equation, the velocity of the fluid increases as the cross section of the pipe decreases. The increase in the velocity of the fluid results in a decrease in pressure, according to the energy balance defined by Bernoulli. This effect is called the Venturi effect, and it is the point of the fluid with the highest velocity, and therefore the lowest pressure, within the narrowest area of the Venturi, also called the throat.
[0053] The use of a Venturi makes it possible to bring the microplastics transported by the water circulating through the main line of the Venturi into contact with a suspension of magnetic iron material particles supplied by a line connected to the throat of the Venturi. At the mixing point where both flows come into contact (the point of lowest pressure and highest velocity, called the throat of the Venturi), the right conditions for the formation of microplastic / magnetic iron material agglomerates surprisingly occur, despite the fact that the residence time at this point is very short (less than 50 thousandths of a second, in particular less than 10 milliseconds, preferably between 5 and 10 milliseconds, more preferably about 7 milliseconds).
[0054] In particular, the venturi design used is such as to provide a circulation at the throat with a Reynolds number (a dimensionless number commonly used in fluid mechanics to characterize flow rates, Re=fluid velocity*pipe diameter*fluid density÷fluid viscosity) of more than 2100, preferably more than 8200. The upper limit of this Reynolds value corresponds to the velocity that causes fluid cavitation.
[0055] In particular, no further mixing step is carried out between steps c) and d).
[0056] Finally, a step d) is carried out in which the free magnetic iron particles and the microplastics / magnetic iron particle agglomerates of step c) are separated from the water by means of a magnetic filter.
[0057] Both the magnetic ferrous particles, which at a selected size have magnetic properties, and the plastic / magnetic ferrous particle agglomerates, which also have these properties due to the very presence of the magnetic ferrous particles, are separated from the water by applying a magnetic field in what is called a magnetic filter. The magnetic filter can have different designs, provided that a very small distance is ensured between the system of magnets used in the filter and the microplastic / magnetic ferrous particle agglomerates present in the water.
[0058] The design of the magnetic filter may vary depending on the application of the separation system. For example, when sampling microplastics in a water matrix, the magnetic filter may present a significant pressure drop, considering that the goal is that the microplastics do not pass through. In this case, the number of magnetic bars forming the filter must be such that the distance between these bars ensures complete separation of the magnetic particles (magnetic iron material or microplastic / magnetic iron material aggregates) entrained in the water. The flow rate of the aqueous matrix for sampling microplastics is relatively low, and the filter can be disassembled to recover the retained magnetic particles for later analysis. For example, if the system is used to treat water containing microplastics to remove them, it is advantageous for the design of the filter not to present a high pressure drop for the circulation of the water and to retain the maximum number of particles to avoid further processing. In this case, it is not necessary to disassemble the filter and completely recover the retained magnetic particles, but rather the filter can be washed countercurrently with a high-velocity water flow to capture the magnetic particles retained by the magnet.
[0059] In a particular embodiment, the magnetic filter is a bar-equipped magnetic filter, which is formed by a set of magnetic bars with almost no separation between each bar, with dimensions between 0.5 cm and 5 cm, on whose surface the magnetic particles (microplastic / magnetic iron material aggregates and the free magnetic iron material itself) contained in the aqueous matrix are deposited.
[0060] The process of the present invention is run continuously, that is, the water to be treated is not charged to a tank in a batchwise manner, but rather is supplied continuously while the process is running.
[0061] Illustrative examples are set forth below to disclose the features and advantages of the present invention, but they should not be construed as limiting the scope of the invention as defined in the claims. EXAMPLES
[0062] Materials and Methods Determining the particle size and shape of microplastics In the present invention, microplastics were added to an aqueous matrix and then subjected to magnetic separation by the process described herein. The particle size range of the microplastics was pre-determined by sieving using different size sieves (5 mm, 1 mm, 500 μm, 250 μm, 100 μm, 50 μm, 20 μm).
[0063] Measuring the size of microplastics in a real aqueous matrix involves their prior separation from the aqueous matrix by vacuum filtration using a microporous membrane filter with a pore size of 0.1 μm or less, and their subsequent drying at room temperature or in a drying oven at a temperature of 100 ° C or less. The filters containing the microplastics are then analyzed by optical microscopy. In this case, a Nikon Eclipse Ci-S / Ci-L upright optical microscope equipped with a DS-Fi2 digital camera and a DS-U3 control unit, with software for measuring and processing the images (NIS-Elements L Imaging), was used. A JEOL JSM 6335F scanning electron microscope with an amplification of 10x to 500.000x was also used. The length and width of the microplastics are measured and the size of the largest dimension (length) is assigned. The shape of the microplastics is analyzed by observing images of the particles at different magnifications.
[0064] Determining the composition of microplastics The composition of the microplastics was determined by Fourier transform infrared spectroscopy (FTIR). The microplastic samples were analyzed according to the conventional analytical method using KBr pellets. Pellets were prepared by adding 1 mg of the microplastic sample and approximately 99 mg of KBr. The resulting powder mixture was compressed by applying a pressure of 10 tons by a hydraulic press to obtain KBr pellets. The samples were then analyzed using a Spectrum Two spectrophotometer (Perkin Elmer). The transmission test was performed at 4000-450 cm -1 The spectra obtained were compared to a library database to determine the type of polymer forming the microplastics using Perkin Elmer Spectrum Software.
[0065] Determination of particle size of magnetic ferrous materials The particle size (mean diameter) and particle distribution of the magnetic ferrous material were determined by scanning electron microscopy analysis of the dry material. The instrument used was a JEOL JSM 6335F with amplification from 10x to 500.000x. The length and width of the magnetic ferrous material particles were measured and assigned a size of the largest dimension (length). For the determination of the particle size distribution, it is appropriate to use the statistics D10, D50, D90, which capture 10%, 50% and 90% of the accumulated particles by volume.
[0066] Determination of iron percentage The iron content of the magnetic ferrous material was determined using a total reflection X-ray fluorescence (TXRF) spectrometer, i.e., S2 Picofox (Bruker) model equipped with a molybdenum source. The sample preparation method consisted of open vessel digestion of the sample with a solution of hydrochloric, nitric and hydrofluoric acids in a volume ratio of 6:2:0.5 at 105 °C for 1.5 hours. The concentration of the material in the vessel was 1000 mg / L and a total volume of 10 mL was used. If necessary, the magnetic ferrous material was pre-ground to a size of less than 100 μm. Once the material sample was digested, an internal gallium standard was added to the solution for later quantification. A 3 μL aliquot of the resulting solution was introduced into the analytical spectrometer and run at 50 kV and 600 μA with an acquisition time of 500 seconds. Integration of the peak corresponding to iron in the resulting spectrogram allowed the weight percentage of iron contained in the material to be determined.
[0067] X-ray diffraction Identification and characterization of the crystalline phases present in the magnetic iron material was performed using powder X-ray diffraction (PXRD). Samples were analyzed on a Panalytical X'Pert PRO theta / theta diffractometer equipped with a Cu tube (Kα radiation, 8.04 keV). The diffractometer has a secondary graphite monochromator and a Xe gas detector. Theta / 2theta scans were performed in the 2θ range of 10-80°, with an angle increment of 0.04°, and an accumulation time of 4 seconds. Prior to analysis, magnetic iron material particles were milled to a size of less than 100 μm, if necessary. High Score Plus software and the ICDD (International Centre for Diffraction Data) PDF-4 Full File crystallography database were used to identify the crystalline phases present in the obtained diffractograms.
[0068] Determining magnetic saturation The magnetic properties of the magnetic iron materials were measured using a Quantum Design MPMS XL-5 magnetometer equipped with a SQUID (Superconducting Quantum Interference Device) sensor. If necessary, the magnetic iron materials were pre-ground to a size of less than 100 μm. The magnetic moment (M) of the magnetic iron materials is −10,000 to 10,000 Oe (−797,700 to 797,700 A m in SI) at room temperature. -1 The magnetic saturation value is the value of M reached when any subsequent increase in H does not cause an increase in the magnetization of the material.
[0069] Determination of particles in suspension Generally, in this study, the determination of particles in suspension was carried out by the method described in the standard UNE-IN 872 for the determination of particles in suspension using vacuum filtration. In that sense, a known volume of the aqueous matrix to be analyzed was filtered through a glass fiber filter of known weight using a device under vacuum or low pressure. The filter containing the retained particles was then dried at 105°C and the particle mass was determined by weight difference against the original filter. In the described example, vacuum filtration was carried out using a microporous membrane filter with a pore size of 0.45 μm. The filter with the solids was then dried in a drying oven at 105°C for 2 hours. Once dried and cooled, the filter containing the solids was weighed on a precision scale and the mass of the solids was determined by weight difference against the same filter before carrying out the separation process.
[0070] Example 1. Formation of Microplastic / Magnetic Ferrous Material Agglomerates Using a Venturi Device Experiments were carried out to confirm the formation of agglomerates due to the interaction between microplastics present in the aqueous stream and magnetic iron material (magnetite) particles fed in the form of a suspension through the throat of a Venturi device (Figure 1). The Venturi device used has a diameter of 25 mm at the inlet and 3 mm at the throat. The magnetite used was pre-ground and had a mean particle diameter of 0.2 μm under dry conditions and a particle size distribution as shown in Figure 2. The crystalline nature of the magnetite used was confirmed by X-ray diffraction analysis, which also showed that the only phase present in the solid was magnetite (Fe 3 O 4 The percentage of magnetic iron minerals used was in the range of 68-78% by weight. In turn, the magnetic saturation values of the materials were in the range of 70-90 emu / g, which is 70·10 in SI units. 3 ~90·10 3 Corresponds to A / m.
[0071] Experiments on the formation of microplastic / magnetic iron material aggregates in the Venturi device were carried out using a water flow (main stream) containing a microplastic concentration of 20 mg / L. Tests were carried out using three different microplastics with similar average particle diameters comprised between 100 μm and 250 μm. The selected microplastics were polystyrene, polyethylene, and polypropylene. In all cases, the flow rate of the main water flow containing microplastics fed to the Venturi was 450 L / h. A conduit was connected to the throat of the Venturi device, allowing the aspiration of a magnetite suspension (average diameter 0.2 μm under dry conditions) held under constant stirring in an attached 50 L tank as a result of the Venturi effect. The concentration of the magnetite suspension was 10 g / L and the flow rate introduced through the throat of the Venturi device was 20 L / h in all cases. Under these conditions, the residence time of the water in the mixing zone was about 7 ms. The formation of aggregates at the outlet of the Venturi was observed in all cases. The formed aggregates were separated from the water by a bar magnetic filter, i.e. a commercial filter (Selter SA) formed by a stainless steel casing inside which six neodymium bar magnets of 1.8 cm diameter and 15 cm length were placed at 2 cm intervals.
[0072] The plastics before passing through the Venturi and the microplastic / magnetic iron material aggregates formed at the Venturi outlet were characterized by transmission electron microscopy (Figures 3 to 8). Effective formation of microplastic / magnetic iron material aggregates in the Venturi device was confirmed.
[0073] Example 2. Yields in the separation of microplastic / magnetite aggregates formed and separated from water by a Venturi system Experiments were carried out to verify the effectiveness of separation of microplastic / magnetic ferrous material aggregates formed using a Venturi device from water, both with the aim of developing an effective treatment process and using this technique as the basis for the design of a microplastic sampler. The Venturi device used has a diameter of 25 mm at the inlet and 3 mm at the throat.
[0074] The experiments were carried out using a water flow (main stream) containing a microplastic concentration of 15 mg / L. Less favorable conditions than those used in Example 1 were chosen to carry out the tests using a fraction of microplastics with a larger average particle diameter comprised between 1 mm and 500 μm, which reduced the microplastic surface / mass ratio. The microplastics selected were again polystyrene, polyethylene, and polypropylene. The flow rate of the main water flow containing microplastics fed to the Venturi device was set between 350 L / h and 425 L / h for the different tests. A conduit was connected to the throat of the Venturi device, allowing the suction of a magnetite suspension (average diameter 0.2 μm under dry conditions) held under constant stirring in an attached 50 L tank as a result of the Venturi effect. The concentration of the magnetite suspension was 10 g / L and the flow rate introduced ranged between 20 L / h and 40 L / h depending on the test. In this particular example, a commercially available filter (Selter SA) formed by a stainless steel casing with six neodymium bar magnets, 1.8 cm in diameter and 15 cm in length, spaced 2 cm apart inside, was used to retain the microplastic / magnetic ferrous aggregates and free magnetic ferrous material in the water stream exiting the Venturi device. The results obtained and the operating conditions used are included in Table 1.
[0075] Table 1. Experimental conditions and separation yields obtained for the separation of microplastics from water using a Venturi device and a magnetic filter. [Table 1]
[0076] The process used showed very efficient separation of microplastics with average particle diameters larger than 500 μm (and smaller than 1 mm). The yield of separation of microplastics / magnetic iron material aggregates in the magnetic filter, and therefore the yield of microplastic retention, was slightly lower than that of free magnetite particles. This is due to the fact that the free magnetite particles have a larger magnetic field relative to their size. The separation yield can be increased by optimizing the design of the magnetic filter used, which improves the effectiveness of separation of microplastics / magnetic iron material aggregates in the magnetic filter, and therefore the yield of microplastic retention.
[0077] Example 3. Non-formation of aggregates between inorganic particles (sand, silicon oxide) and magnetite using a Venturi system Experiments were carried out to verify the formation of aggregates due to the interaction between sand grains present in an aqueous stream and magnetic iron material (magnetite) particles fed in the form of a suspension through the throat of a Venturi device (Figure 2). The Venturi device used has a diameter of 25 mm at the inlet and 3 mm at the throat.
[0078] The experiments in the Venturi device were carried out using a water flow (main stream) containing a concentration of sand with an average particle diameter between 100 μm and 250 μm in a suspension (silicon oxide) of 20 mg / L. The flow rate of the main water flow containing sand in suspension fed to the Venturi was 450 L / h. A conduit was connected to the throat of the Venturi device, allowing the suction of a magnetite suspension (average diameter 0.2 μm under dry conditions) held under constant stirring in an attached 50 L tank as a result of the Venturi effect. The concentration of the magnetite suspension was 10 g / L and the flow rate introduced through the throat of the Venturi device was in all cases 20 L / h. Under these conditions, the residence time of the water in the mixing zone was about 7 ms.
[0079] As can be seen in FIG. 9, in this case no sand / magnetic iron material aggregates were formed even after following the same operating conditions that were positive for microplastics.
Claims
1. A process for separating microplastics from an aqueous matrix, comprising: a) providing an aqueous matrix containing microplastics; b) providing a suspension of magnetic ferrous particles in water; c) passing said aqueous matrix of step a) through a venturi device and contacting it at the throat of said venturi device with said suspension of magnetic material particles in water from step b) to form microplastic / magnetic ferrous material particle agglomerates; d) separating the liberated magnetic iron particles from step c) and the microplastics / magnetic iron particle agglomerates by a magnetic filter; A process including.
2. 2. The process of claim 1, wherein the microplastics are selected from the group consisting of polystyrene (PS), polyethylene (PE), including high density polyethylene (HDPE) and low density polyethylene (LDPE), polypropylene (PP), polyethylene terephthalate (PET), polyvinyl chloride (PVC), polycarbonate (PC) and polyurethane (PU), and mixtures thereof.
3. 3. The process of claim 2, wherein the microplastics are selected from the group consisting of polystyrene (PS), polyethylene (PE), including high density polyethylene (HDPE) and low density polyethylene (LDPE), polypropylene (PP), and mixtures thereof.
4. 4. The process according to any one of claims 1 to 3, wherein the average diameter of the microplastics is in the range of 0.1 μm to 500 μm.
5. The process according to any of claims 1 to 4, wherein the aqueous matrix of step a) is provided at a flow rate of 0.01 to 1000 L / s, preferably 300 to 600 L / h.
6. The process of any of claims 1 to 5, wherein the magnetic iron material comprises an iron species selected from the group consisting of Fe(II), Fe(III), metallic Fe, and mixtures thereof.
7. 7. The process of claim 6, wherein the magnetic iron material is magnetite.
8. The process according to any of the preceding claims, wherein the average diameter of the magnetic material is comprised between 0.05 μm and 100 μm.
9. 9. The process according to claim 8, wherein the average diameter of the magnetic material is comprised between 0.1 μm and 10 μm.
10. The process according to any of the preceding claims, wherein the concentration of magnetic material in the suspension of step b) is between 1 mg / L and 100 g / L.
11. The process according to any of the preceding claims, wherein the suspension of step b) is provided at a flow rate of 0.001 to 100 L / s, preferably 5 to 50 L / h.
12. 12. The process according to any of claims 1 to 11, wherein the inlet flow rate of the aqueous matrix in the throat of the venturi in step c) is between 0.01 and 1000 L / s, preferably between 300 and 600 L / h, and / or the inlet flow rate of the suspension of magnetic particles in water in the throat of the venturi in step c) is between 0.001 and 100 L / s, preferably between 5 and 50 L / h.
13. A process according to any preceding claim, wherein the throat diameter of the Venturi device represents a 75% to 99% reduction relative to the pipe diameter.
14. The process according to any of claims 1 to 13, wherein the magnetic filter of step d) is a magnetic filter with bars.